2018
DOI: 10.1128/mbio.01751-18
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in the First 2 Years of Life and the Association with Body Mass Index at Age 12 in a Norwegian Birth Cohort

Abstract: Understanding the role of the early-life gut microbiota in obesity is important because there may be opportunities for preventive strategies. We examined the relationships between infant gut microbiota at six times during the first two years of life and BMI at age 12 in a birth cohort of 165 children and their mothers. We found that the gut microbiota from early life to two years shows an increasingly strong association with childhood BMI. This study provides preliminary evidence that the gut microbiome at 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 58 publications
3
94
1
1
Order By: Relevance
“…A previous birth cohort study from Canada found that compared to breastfed infants, formula fed infants had greater diversity at 3 months of age, but lower diversity at 1 year [30]. Another study found that higher diversity at 3 months of age is associated with higher risk for overweight later in life [31]. As such, we postulate that higher diversity in early infancy, before the gut microbiome has become adult-like, may reflect a less healthy gut microbiome and portend risk for future development of chronic disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous birth cohort study from Canada found that compared to breastfed infants, formula fed infants had greater diversity at 3 months of age, but lower diversity at 1 year [30]. Another study found that higher diversity at 3 months of age is associated with higher risk for overweight later in life [31]. As such, we postulate that higher diversity in early infancy, before the gut microbiome has become adult-like, may reflect a less healthy gut microbiome and portend risk for future development of chronic disease.…”
Section: Discussionmentioning
confidence: 98%
“…All multivariable models included birth weight (kg) and gestational age (weeks) as continuous except for the Shannon diversity models, in which we split these covariates at the median to allow model convergence. We adjusted for these potential confounders based on prior literature [13,31,70,71], which indicated these variables were associated with both our exposure and outcome, but were not on the causal pathway. We conducted additional covariate-adjusted analyses to ensure our findings were robust to model adjustment for alternative categorizations of breastfeeding or to model adjustment for infant age at stool sample collection, maternal education, and maternal smoking.…”
Section: Model Adjustments and Statistical Significance Thresholdsmentioning
confidence: 99%
“…This difference during early development is believed to influence the likelihood of developing health problems later in life such as overweight/obesity and diabetes (1)(2)(3). Although the detailed mechanism has not been fully elucidated, disruption of early-life gut microbiota may precede the development of obesity during childhood (4)(5)(6). In addition, the high protein content in infant formula has been shown to be a factor that is responsible for stimulation of higher insulin and insulin growth factor 1 (IGF-1) leading to rapid weight gain, while disfavoring the use of fat via lipolysis [the "early protein hypothesis" (7)].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the structure of the gut microbial community, which includes its diversity and composition, has significant implications for human development including the maturation of the enteric system, training of the immune system (Y. K. Lee & Mazmanian, ; Torrazza & Neu, ), and brain development (Heijtz et al, ). The community structure of the gut microbiota in early life is also associated with later health outcomes including risk of obesity, insulin resistance, and the development of asthma and allergies (Cani, Delzenne, Amar, & Burcelin, ; Frati et al, ; Kozyrskyj, Bahreinian, & Azad, ; Le Chatelier et al, ; Stanislawski et al, ; Thompson, ; Vatanen et al, ). Thus, understanding the factors that shape the diversity and composition of the gut microbiota during a critical period of its development is important.…”
Section: Introductionmentioning
confidence: 99%